Perilaku Pemilih dan Partisipasi Pemilih Dalam Pilkada Kota Sukabumi Tahun 2024 - Ratna Istianah; Akbar Devriansyah; Arti Putri Apandi; Annisa Fauziah (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
The voter participation rate in the 2024 Sukabumi City Regional Election has not reached the 80% target set by the General Election Commission (KPU), with an average achievement of only 69.78%. This low number shows that there are obstacles in people's political involvement, one of which is related to voter behavior. This study aims to analyze the influence of voter behavior on the level of participation in the Regional Elections. Voter behavior is studied through sociological, psychological, and rational approaches. In Sukabumi City, voter behavior tends to be rational-pragmatic, namely voting based on considerations of direct benefits and concrete personal interests. This research uses a mixed method, with data collection through surveys, interviews, and documentation. The results of the regression analysis showed that voter behavior had a significant effect on participation, both individually and collectively. The conclusion of this study states that voter behavior, especially those that are rational-pragmatic, contribute positively to increasing participation in the Sukabumi City Regional Elections